2022
DOI: 10.3390/su141811786
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Approach for the Detection of Noise Type in Ancient Images

Abstract: Recent innovations in digital image capturing techniques facilitate the capture of stationary and moving objects. The images can be easily captured via high-end digital cameras, mobile phones and other handheld devices. Most of the time, captured images vary compared to actual objects. The captured images may be contaminated by dark, grey shades and undesirable black spots. There are various reasons for contamination, such as atmospheric conditions, limitations of capturing device and human errors. There are v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In an exploration of innovations in digital image processing, Pawar et al [2] delve into the complexities of image contamination caused by various factors such as atmospheric conditions and device limitations. By employing advanced image processing techniques, these researchers emphasize the crucial significance of accurate noise detection for subsequent restoration.…”
Section: Special Issue Coveragementioning
confidence: 99%
“…In an exploration of innovations in digital image processing, Pawar et al [2] delve into the complexities of image contamination caused by various factors such as atmospheric conditions and device limitations. By employing advanced image processing techniques, these researchers emphasize the crucial significance of accurate noise detection for subsequent restoration.…”
Section: Special Issue Coveragementioning
confidence: 99%
“…The distortions can lead to mistakes in mural identification and classification, while traditional restoration of damaged artworks requires talented artisans, which are difficult to find these days. Therefore, virtual restoration of the murals may have great potential for mural conservation and research [ 17 , 135 ]. Using computer technology, digitally repaired damaged murals can be helpful for the virtual display of the murals, and it has been shown that cloud edge computing could be a useful tool to automatically identify and repair the cracks of murals [ 136 ].…”
Section: Measures For Mural Restoration and Protectionmentioning
confidence: 99%
“…It has been proposed that a multi-path convolutional neural network, which takes multiple lighted image patches as inputs and outputs the corresponding label of the center pixel, can rapidly detect mural deterioration [ 144 ]. Recently, machine learning methods have been widely for murals study, which can improve the accuracy of composition detection [ 16 , 17 ]. In addition, based on pigments and physical strata of the murals from multi-band imaging techniques, it is possible to virtually reconstruct the original color and appearance of the faded murals.…”
Section: Emerging Opportunities and Challenges For Mural Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the field of medical imaging, obtaining pristine medical scans is often limited by equipment availability and financial constraints (Trepani et al 2021). Similarly, in artistic applications, capturing flawless photographs under varying lighting conditions can be a costly endeavor (Pawar et al 2022). The industrial sector faces challenges when dealing with noisy sensor data due to equipment limitations (Radlak et al 2020).…”
Section: Introductionmentioning
confidence: 99%